Fatigue dan status nutrisi pada pasien dengan kanker payudara yang menjalani kemoterapi - Sapti Ayubbana; Sari Narulita (Holistik Jurnal Kesehatan, 2020)
Fatigue and nutritional status in patients with breast cancer undergoing chemotherapyBackground: Breast cancer is one type of cancer and is one of the leading causes of death in the world. Cancer patients who receive chemotherapy are at risk of impaired nutritional status due to the disease and its treatment. Chemotherapy treatment can have side effects on the gastrointestinal system such as nausea, vomiting, stomatitis, anorexia, changes in taste. These side effects can cause the patient's nutritional intake to decrease. Cancer and its treatment can cause fatigue complaints.Purpose: to identify the relationship between fatigue and nutritional status in patients with breast cancer patients undergoing chemotherapyMethods: The design of this study was quantitative using a cross sectional approach. The population in this study were patients with breast cancer undergoing chemotherapy. This research was conducted at Dr.H. Abdul Moeloek Hospital of Lampung Province with 42 respondents.Results: Spearman correlation test results found that nutritional status variables have a significant relationship with fatigue (p value = 0.031) with moderate correlation strength (r = 0.471).Conclusion: The nursing intervention on the side effects of chemotherapy treatment which has a positive effect on nutritional conditions in an effort to overcome nutritional disorders and complaints of fatigue in cancer patients.Keywords: Breast Cancer; Chemotherapy; Fatigue; Nutritional StatusPendahuluan: Kanker payudara merupakan salah satu jenis kanker dan menjadi salah satu penyebab kematian di dunia. Pasien kanker yang menerima kemoterapi memiliki resiko gangguan status nutrisi akibat penyakit dan pengobatannya. Pengobatan kemoterapi dapat memberikan efek samping terhadap sistem ganstrointestinal seperti mual, muntah, stomatitis, anoreksia, perubahan rasa. Efek samping tersebut dapat menyebabkan asupan nutrisi pasien dapat mengalami penurunan. Kanker dan pengobatannya dapat menyebabkan keluhan fatigue.Tujuan: Mengetahui adanya hubungan antara status nutrisi terhadap fatigue pada pasien kanker payudara yang menjalani kemoterapi.Metode: Desain penelitian ini adalah kuantitatif dengan menggunakan pendekatan cross sectional . Populasi pada penelitian ini adalah pasien dengan kanker payudara yang menjalani kemoterapi. Penelitian ini dilakukan di RSUD Dr.H. Abdul Moeloek Provinsi Lampung dengan 42 responden.Hasil: Pada uji korelasi spearman didapatkan bahwa variabel status nutrisi mempunyai hubungan yang bermakna dengan fatigue ( p value = 0,031) dengan kekuatan korelasi sedang (r = 0,471).Simpulan: Kesimpulan diperlukan intervensi keperawatan terhadap efek samping pengobatan kemoterapi yang berdapak terhadap kondisi nutrisi dalam upaya mengatasigangguan nutrisi dan keluhan fatigue pada pasien kanker